Community Assistance In Increasing Knowledge As The Effort To Prevent Covid-19 In Communities With Hypertension - Mariana; Pariyana; Agita Diora Fitri; Muhammad Aziz (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2021)
Hypertension is one of the comorbidities found in COVID-19 patients. The severity of COVID-19 in comorbid hypertension is important to prevent by controlling risk factors and conducting early detection. Community coverage for early detection is still low due to low awareness of the importance of prevention. The purpose of this activity is to increase public knowledge through the provision of counseling regarding the prevention of COVID-19. The target audience for community service activities in this activity is hypertension patients in the working area of the Merdeka Palembang Health Center. The number of targets for this activity is 25 people. The method of implementing this activity is with lectures and discussions. Conduct pretest and posttest to assess knowledge before and before counseling regarding prevention of COVID-19 in people with hypertension. The results of this activity are characteristics of respondents based on age, most of them are in late adulthood (36-45 years) as many as 13 people (52%). Most of them are male many as 15 people (60%), high school education level or equivalent as many as 22 people (88%) and, most of them work as private employees as many as 12 people (48%). The results of the statistical test using the Wilcoxon p-value = 0.000, which show that there are differences in public knowledge before and after counseling regarding the prevention of COVID-19.